Different intervals of behavioral observation in the scanning method and the real behavior of pigs - De Oliveira, Geyssane Farias [UNESP]; Caldara, Fabiana Ribeiro; Garcia, Rodrigo Garofallo; Seno, Leonardo De Oliveira; Marcon, Adila Vasconcelos; Foppa, Luciana; Martins, Renata Aparecida; Crone, Carla (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2018)
The objective of this work was to study the behavior of swine females in the grower phase using different observation intervals (continuous, 5, and 10 min). A total of 42 swine were used, 14 of them for each treatment, which were identified with a marker stick. These animals were observed using the focal sampling method for 5 h. The treatments were the observation intervals: continuous, every 5 min, and every 10 min. Among the behaviors analyzed during the experiment, the different observation intervals did not affect the estimated time spent in the activities. Time observation intervals of 10 min or less adequately describe the duration of the main behavioral parameters of female pigs in this setting.
Keywords: ethology; pig production; social behavior